Navigating Religious Hegemony and Human Rights Based on KUHP: Al-Zaytun's Controversial Case - Dewantri, Puja Alviana; Pattiserlihun, Selvone Christin; Hakim, Putri Rahmah Nur (POROS ONIM: Jurnal Sosial Keagamaan, 2023)
The Al-Zaytun issue has ignited a heated debate in Indonesia about religious pluralism, religious freedom, and human rights. This quandary, reminiscent of the Indonesian Ahmadiyya Muslim Congregation's situation classified as "heretical," demonstrates the historical tendency to pigeonhole alternative ideas. This highlights the hidden presence of takfiri ideology, a potentially divisive force despite its relative obscurity. In this context, this article examines the contentious Al-Zaytun case, in which the rejection of non-traditional Islamic teachings prompts a broader examination of the conflict between entrenched traditional practices, which represent the majority of Indonesian Muslims, and fundamental human rights principles, particularly religious freedom. Using an analytical method, it dissects media portrayals and examines the legal framework established by KUHP 2023, addressing religious violations and belief-based areas. The essay explores the case's potential under the prior KUHP 2021 through comparative research, revealing the various issues of interpreting and applying legislation in cases of blasphemy and religious disagreements. The study says that varied Sharia interpretations within Islam should not be used to justify restricting religious freedoms, mirroring Boaventura's interpretation of Talal Asad's discoveries, which confirm Islam's diversity of religious experiences and adaptive Sharia interpretations. Indonesia faces the challenge of cultivating a nuanced perspective that preserves individual liberty and communal harmony while balancing the intricate interaction of religious dynamics, legal systems, and human rights.